Analysis oft the friction coefficient in fabrics made from non-conventional blends - Lima, Mário (2009)
Most textile materials are used and touched by the human skin, in particular the hand. Traditionally, the quality and surface characteristics of apparel fabrics are evaluated by touching and feeling, leading to a subjective assessment. For this reason, the interaction with the human senses is an essential performance property. When touched by the human hand, friction is one of the first feelings and therefore friction coefficient is ail important parameter. This paper describes a new patented laboratory instrument, which was investigated and deigned at tire University of Minho based on a different method of accessing friction coefficient of fabrics, as well as its fundamentals and working principle. This is followed by an experimental study, where it comparison between three different double-faced fabrics made with non-conventional fibre combinations was performed under controlled atmosphere. The tested materials are:1) Polyester/Cotton-Soya Fibre (PES/CO-SPF)2) Polyester/Cotton-Corn fibre (PES/CO-PLA, Polylactic-acid)3) Polyester/Cotton- Cotton (PES/CO-CO)The results of the experimental work are analysed using various tools, including SPSS 14.0 (R) statistical package and commented in the light of the influence of the raw material in the friction properties of the fabrics.